PENGARUH KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA (Studi pada Dinas Perindustrian dan Perdagangan Provinsi Jawa Tengah) - 14.05.51.0058, Adik Siti Barokah; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2018)
The purpose of this research test the influence of leadership, motivation, and discipline work of the performance of employees.The study is done in the industry and trade provincial central java. A method of the sample collection in this research using a technique conveniance sampling with a period research 2014-2016.Kuosioner used as data collection method. The sample of the in research namely 69 respondents employees office of industry and trade provincial central java. Regression analysis linear multiple with software spss 20 used to test hypotheses research. This research result indicates: leadership, motivation, and discipline work significant on performance. Leadership is not significant on performance, motivation influential positively and significant impact on performance, discipline work not significant on performance . R2 to research this is of 39,9 %, this means that model research that could explain 39,9 % for the performance, while 60,1 % described by other variables that not included in this research.Keywords: leadership, motivation, discipline work, performance